Integração: o desenvolvimento como conseqüência da integração dos Estados-membros nos paradigmas supranacional e intergovernamental - Furtado, Marina Locci (2008)
This study analyses two paradigms of regional integration, the European Union, as the most advanced model and the Mercosul. The purposes of this study is to analyze the possibility of promoting of development in the member-states within the regional integration and the regional integration too, breaking the paradigms, showing the possibility of becoming true the integration through different models as the Mercosul, and not only through the supranational European model. The purpose of this essay is to demonstrate which would be the necessary development to the States, as for the regional integration, independently of the model adopted and developed taking into account the dynamics in the economy and human development of each country. During this study, firstly, it will be analysed the fundamental elements to the fruition thereof, as the State. Then, we took into consideration the notion of sovereignty, as in the different standards and levels of integration and then the origin thereof based on the development achieved by the States. Using the European Union, as the supranational model of integration and Mercosul as the intergovernmental model, compare the development of the Statemembers, to demonstrate the existence or not of an ideal model of integration